PEMBIASAAN NILAI-NILAI RELEGIUS DI MIS NURUL FURQON KATINGAN: IMPLEMENTASI, TANTANGAN DAN SOLUSI - Raudhatul Jennah; Hamidah (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
This study aims to analyze the patterns of religious habit formation in improving the quality of religious education for students at MIS Nurul Furqon Katingan. The study employs a descriptive qualitative approach, utilizing data collection techniques such as observation, interviews, and documentation involving the school principal, teachers, students, and parents. The results indicate that religious habit formation is not merely a routine activity but is structured within an integrative habit-forming model that encompasses the internalization of values, the reinforcement of worship practices, and the development of moral character through daily school activities. The implementation pattern is carried out systematically through integration into the curriculum, teacher role modeling, and the strengthening of school culture, supported by periodic evaluations and collaboration with parents. Key findings indicate that this model contributes to improved discipline, religious understanding, and the development of Islamic character among students. Despite challenges such as the heterogeneity of family backgrounds and limited resources, the adaptive strategies implemented ensure the program’s sustainability. The implications of this study confirm that religious habit formation based on an integrative model is effective as a strategic approach to improving the quality of religious education at the Islamic elementary school level.